Analysis of Chitinase Enzyme Trichoderma sp. in Degrading Fusarium oxysporum - Rosyida, Risya; Martosudiro, Mintarto; Muhibuddin, Anton (Research Journal of Life Science, 2022)
The chitinase enzyme in Trichoderma sp. play an important role in pathogen control. This is because chitin is the main component of the fungal cell wall which the chitinase enzyme can degrade. One Trichoderma sp. isolate was obtained (UBPK6) with the highest percentage of inhibition against Fusarium oxysporum, 76.71%. In addition, UBPK6 isolates also showed the highest bromocresol purple reagent test results (indicating the presence of chitinase enzymes). Chitinase enzyme activity was measured for Trichoderma asperellum isolates. The results showed that the optimum incubation period for enzyme production was the 4th day, with an enzyme activity value of 4.05 U/mL. It indicates that this time is the right time for harvesting enzymes. Furthermore, the effect of pH on the chitinase enzyme activity of Trichoderma asperellum fungus. The test results showed that the optimum value was produced at pH 5 with a value of 3.4 U/mL and decreased afterward. The pH five treatment was the best in inhibiting the growth of pathogens, with an inhibition value of 60.63%. The higher the content of the chitinase enzyme, the higher its ability to degrade damage to the germination of pathogenic spores, thus causing the growth of the pathogen to be inhibited.